Review of developments in corneal transplantation in the regions of Brazil - Evaluation of corneal transplants in Brazil (Clinics, 2016)
The aim of this study was to identify inequalities in corneal donation and transplantation among the regions of Brazil. A transversal and retrospective study was specifically conducted using data from the Brazilian Transplant Registry collected by the Brazilian Association of Organ Transplantation between January 2002 and December 2014. The collected data were processed using descriptive statistical methods, and p